Minors, bullying and suicide. A case study through spanish reference digital media - Pérez-Virtus, Ander (2018)
Media are supposed to pay special attention to the traditional journalistic ethical norms in the cases of media coverage of bullying in schools (Olweus, 1998; Mason, 2008), insofar as these combine childhood, violence and, in some unfortunate cases, suicide (Herrera et al., 2015). Even if mass media have traditionally avoided these kind of coverage, giving rise to an informative silence that answers to its concern about a possible “imitation effect” (Philips, 1974), it is a fact that the topic has gained attention in the media sphere, probably due a growing public and social interest towards the bullying problem. Because of the scarce researches on media coverage of bullying in schools related to suicide (Müller, 2011), this paper examines the ethical codes and the media treatment of three significant cases in Spain. The results shed light on the consequences of releasing this kind of informative content and on the options to improve this kind of treatment avoiding risk factors.